La rage d'écrire, ou, Le défi féminin dans l'oeuvre de Nicole Brossard - Delepoulle, Anne-Marie (Université de Paris-Val de Marne, 1983)
Keywords: amériques; arts; discipline; mémoires/thèses; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; discipline; droits civiques; fem1000; histoire et politique; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires